Informing the public about a pandemic - Véricourt, Francis de,Gurkan, Huseyin,Wang, Shouqiang (ESMT Berlin, 2021)
This paper explores how governments may efficiently inform the public about an epidemic to induce compliance with their confinement measures. Using an information design framework, we find the government has an incentive to either downplay or exaggerate the severity of the epidemic if it heavily prioritizes the economy over population health or vice versa. Importantly, we find that the level of economic inequality in the population has an effect on these distortions. The more unequal the disease's economic impact on the population is, the less the government exaggerates and the more it downplays the severity of the epidemic. When the government weighs the economy and population health sufficiently equally, however, the government should always be fully transparent about the severity of the epidemic.
urn:nbn:de:101:1-2021030809320505382702
Keywords: Graue Literatur; Public Health; Epidemic Control; Information Design; Strategic Behavior